Variation of Chest Computed Tomographic Findings in Coronavirus Disease-19 (COVID-19) Positive Patients in a Tertiary Care Hospital, Bangladesh (Anwer Khan Modern Medical College Journal, 2023)
Background: We aimed to report different patterns of chest computed tomographic (CT) findings in coronavirus disease-19 (COVID-19) infected patients in Bangladesh.Methods: This was a cross-sectional descriptive study of 200 consecutive reverse transcriptase polymerase chain reaction (RT-PCR) positive patients who underwent CT chest. Distribution, type of abnormal lung findings and Prevalence were recorded.Result: Among the total study cohort of 200 patients, 148(74 %) were males and 52 (26 %) were females with mean age of 53.9 ± 16.7 years (range 20–92 years). We observed lung parenchymal abnormalities in 125 (62.0 %) cases whereas 75 (37.5 %) RT-PCR positive cases had a normal chest CT. Common symptom was cough in 108 (54%), Only 18.0% of the patients were dyspneic. Among the patients with abnormal CT findings bilateral involvement was commonest 98/125 (78.4 %), multilobar (54.0 %) lung involvement with a predominant peripheral and posterior distribution was more commonly observed. With regards to the type of opacity, ground glass opacity (GGO) was the predominant abnormality found in 122/125 cases. Pure GGO was observed in 29 (23.2 %), most common pattern was GGO mixed with consolidation was noted in 52(41.6 %). GGO with crazy paving pattern was seen in 33 (26.4 %) and sub pleural linear and curvilinear lines were seen in 23(18.4%). Peri-lesional or intralesional segmental or subsegmental pulmonary vessel enlargement was observed in 36 (70.6 %) cases.Conclusion: In this study population, we found a high proportion of symptomatic laboratory-confirmed SARS-CoV-2 patients had positive chest CT findings. Patients with a positive CT showed typical findings of predominant GGOs in a bilateral and multilobar distribution with peripheral predilection.AKMMC J 2021; 12(1) : 38-44